Study of Association between Serum Cholinesterase Level, Peradeniya Organophosphorus Poisoning Scaleand Clinical Outcome in Patients with Acute Organophosphorus Poisoning - Devpriya Shukla; Maneesh Jain; Amit Jain (International Journal of Health and Clinical Research, 2021)
Background: Pesticide poisoning accounts for approximately 60% of the estimated 500 000 self-harm deaths in the region each year4. 3 According to many studies, organophosphorus pesticides are responsible for roughly two-thirds of these deaths5—a total of 200 000 per year.Acute organophosphorus poisoning (AOP) is one of the most common medico toxic emergency in India.Serum cholinesterase levels as a diagnostic marker is well established and but as a prognostic marker, evidenceis lacking. Peradeniya organophosphorus poisoning (POP) scale is easily available scoring systems in predicting the severity with clinical outcome. Aims and Objectives:To study the association between serum cholinesterase level, POP scale and clinical outcome in patients with AOP. Methods: Thirty-one patients with AOP were studied at Emergency Department of Sri Aurobindo Medical College and PG Institute, Indore, from December 2017 to May 2019. Estimation of serum cholinesterase levels and categorization based on POP scaleas Mild (0-3), Moderate (4-7) and Severe (8-12) was done and compared with hospital stay, ventilatory support, and mortality. Results: AOP was more prevalent in males (74.2 %). Serum cholinesterase levels of patients had no significant association with total duration of hospitalization (p>0.05) but was significant factor that influenced the clinical outcome (death). POP scale grading of patient with AOP was the significant factor that strongly influence the total duration of hospitalization (p<0.003), duration of ventilator support (p<0.001) and clinical outcome (p<0.001). Conclusions: POP scale is a better prognostic marker due to significant association between POP scale and clinical outcome, requirement, and duration of ventilatory support and total duration of hospitalization.